PENERAPAN PUTUSAN PTUN TERHADAP PEMBERHENTIAN PERANGKAT DESA DITINJAU DARI UNDANG-UNDANG NOMOR 6 TAHUN 2014 - Shelia Ristiana Agustin; Made Warka (Gapenas Publisher, 2022)
State administrative courts are the courts that have the ability to hear cases that have the authority or competence, such as relative competence and absolute competence. These courts have the jurisdiction to hear matters that have the authority or competence. The ability of a court to hear a matter in accordance with the scope of its jurisdiction is referred to as its